Correction: Liu et al. Automatic Extraction for Land Parcels Based on Multi-Scale Segmentation. Land 2024, 13, 158 - Land Editorial Office, Land Editorial Office (Land (Basel), 2024)
The Land Editorial Office would like to make the following correction regarding the academic editor listed in this published paper [...]